2019
DOI: 10.22146/gamaijb.27402
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Manufacturing Flexibility on Business Performance: Malaysian’s Perspective

Abstract: This research aims to investigate the impact of manufacturing flexibility on business performance. The manufacturing flexibility dimensions are mix, new product, labor, machine, material handling, routing and volume flexibility. The measures for the business performance are product market performance, customer satisfaction and profitability. The impact of manufacturing flexibility on business performance has been tested using a cross sectional study employing survey methodology, conducted within five manufactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Moreover, Ghatebi et al (2013), Haque and Islam (2013) Lagat et al (2016), and Manokaran (2019) supported the positive influence of SCMPs (i.e., strategic supplier partnership, customer relationship management practices, level of information sharing, quality of information sharing) on customer satisfaction (i.e., trust, commitment, communication), where researchers revealed the importance of enhancing level of customer satisfaction through managing SCMPs. Therefore, MSMEs should focus on enhancing SCMPs to reach a better customer satisfaction level, and the negative impact of organizational flexibility on customer satisfaction (i.e., trust, commitment, communication) was contradicted with Adara (2020), Fatima et al (2021), Sáenz et al (2018), Tan and Lim (2019), who revealed the positive influence of flexibility on customer satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Ghatebi et al (2013), Haque and Islam (2013) Lagat et al (2016), and Manokaran (2019) supported the positive influence of SCMPs (i.e., strategic supplier partnership, customer relationship management practices, level of information sharing, quality of information sharing) on customer satisfaction (i.e., trust, commitment, communication), where researchers revealed the importance of enhancing level of customer satisfaction through managing SCMPs. Therefore, MSMEs should focus on enhancing SCMPs to reach a better customer satisfaction level, and the negative impact of organizational flexibility on customer satisfaction (i.e., trust, commitment, communication) was contradicted with Adara (2020), Fatima et al (2021), Sáenz et al (2018), Tan and Lim (2019), who revealed the positive influence of flexibility on customer satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Organizational flexibility helps organizations to enhance their customers satisfaction, where flexibility allows organizations to increase their production level to unanticipate customer needs and to reduce waiting time in case of level of demand fluctuated (Sáenz et al, 2018). Several studies investigated the impact of flexibility on customer satisfaction, where Sáenz et al (2018) identified the positive significant impact of flexibility on customer satisfaction in manufacturing companies, while Tan and Lim (2019) illustrated the importance of flexibility practices on enhancing customer satisfaction level in manufacturing industries, whereby Adara (2020) empirically investigated the positive significant impact of volume flexibility on customer satisfaction. Moreover, Yousuf et al (2020) identified that strategic flexibility is considered as a significant technique to react to uncertain situation and improve customer satisfaction in pharmaceutical industries.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…IF may also directly impact customer satisfaction by increasing a firm's ability to respond to their preferences in a better way (Tan and Lim, 2019). IF reduces internal resource constraints (Wei et al.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Although the surveys provide significant evidence for decision-makers, especially the government, studies show other flaws. Most studies on customer satisfaction that use a survey, suffer from survey's inherent flaws, including "the possibility of missing appropriate context and of lacking respondents' knowledge" (Supriyadi, 2010, p. 431) as the survey tends to use a general assumption (Tan & Lim, 2019). To avoid this general assumption, a more subjective approach is needed to explore those studied feelings.…”
Section: Identified Predictors Of Seaport Users' Satisfactionmentioning
confidence: 99%